Application of Flipped Classroom to Discovery Learning Models to Increase Student Participation in Biology Online Learning - Togatorop, Sondang Rosita Indah; Dito, Samuel Benny (Bioedusiana: Jurnal Pendidikan Biologi, 2022)
The purpose of this study is to increase student participation in biology online learning by applying flipped classroom to discovery learning models. This research was conducted at SMA Negeri 22 Jakarta in July to November 2021 during the Covid-19 pandemic using action research methods consisting of three cycles, each cycle consisting of two meetings. Research instruments in the form of questionnaire sheets in pre-cycles made digitally using google form (GF) and observation sheets (observations) to observe students' participation in online biological learning (in the network), observation sheets (observations) to observe the implementation of learning activities. The data obtained is then analyzed by calculating the percentage of student participation to see the trends that occur in biology learning activities online. There are four aspects of online learning participation, namely self-study and making material summaries and uploading material summaries, attending virtual face-to-face meetings, discussions and cooperation in groups through whatsapp groups, and uploading group tasks on time. The results showed increased student participation in every aspect of cycle I, cycle II, and cycle III. The average percentage of student participation in cycle I, cycle II, and cycle II is 65.97, 84.02, and 93.05, respectively. Based on the results of the study, it can be concluded that the application of flipped classroom in discovery learning models can be used as an effort to increase student participation in biology online learning.